Structural Analysis Program Using Direct Stiffness Method for The Design of Reinforced Concrete Column - Ahmad Faza Azmi (Fakultas Teknik Universitas Bhayangkara, 2017)
Most of the analyzes and calculations in civil engineering have been using computer. But many commercial structuralanalysis programs are relatively expensive. Hence one of the alternative way is using a self developed structuralanalysis program. The computer program is constructed using Visual Basic 6 programming language. Using directstiffness method and theory of ACI 318-02, a numerical procedure along with a computer program was developed forthe structural analysis and design of reinforced concrete member. From the direct stiffness method,in terms ofstructural analysis, the output that obtained from the program are internal element forces and support reactions nodedisplacements. From ACI 318-02 codes, in terms of reinforced concrete member analysis, the program generate theamount of longitudinal and lateral reinforcement of concrete member based on the output in the previous structureanalysis program. The program also reveals the biaxial bending-axial interaction diagrams in each direction ofrectangular and circular column. The interaction diagram of the columns is a visual representation to determine themaximum axial load and moment exceeded the capacity of the column.